Projected Impacts of Climate Change on Drought Patterns Over East Africa - Haile, Gebremedhin Gebremeskel; Tang, Qiuhong; Hosseini‐Moghari, Seyed‐Mohammad; Liu, Xingcai; Gebremicael, T. G.; Leng, Guoyong; Kebede, Asfaw; Xu, Ximeng; Yun, Xiaobo (Earth's future, 2020)
Investigation of the pressing impacts of climate change on drought is vital for sustainable societal and ecosystem functioning. The magnitude of how much the drought will change and the way how droughts would affect society and the environment are inadequately addressed over East Africa. This study aimed at assessing future drought changes using an ensemble of five Global Climate Models (GCMs) in the Coupled Model Intercomparison Project (CMIP5) over East Africa. To this end, drought characteristics were investigated under the Representative Concentration Pathways (RCPs) 2.6, 4.5, and 8.5 in the near term (the 2020s; 2011–2040), midcentury (2050s; 2041–2070), and end of century (2080s; 2071–2,100). The changes of the Standardized Precipitation Index (SPI) and Standardized Precipitation‐Evapotranspiration Index (SPEI) were first compared, and the SPEI was used for measuring future droughts as it showed stronger changes due to its inclusion of temperature effects. Drought area in East Africa is likely to increase at the end of the 21st century by 16%, 36%, and 54% under RCP 2.6, 4.5, and 8.5, respectively, with the areas affected by extreme drought increasing more rapidly than severe and moderate droughts. Spatially, drought event, duration, frequency and intensity would increase in Sudan, Tanzania, Somalia, and South Sudan, but generally decrease in Kenya, Uganda, and Ethiopian highlands. Results also confirm that drought changes over East Africa follow the “dry gets drier and wet gets wetter” paradigm. The findings provide important guidance for improving identification of causes, minimizing the impacts and enhancing the resilience to droughts in East Africa. Key Points We examined the impact of changes in precipitation and temperature on drought characteristics over East Africa during 1981–2099 Precipitation and temperature will increase over East Africa; however, the temperature impact is dominant leading to extreme droughts Drought area in East Africa is likely to increase at the end of the 21st century by 16%, 37%, and 54% under RCP 2.6, 4.5, and 8.5, respectively